Opioid Use Disorder in Pregnancy. (31st May 2017) - Roper, Van; Cox, Kim J.
Abstract : Opioid use disorder (OUD) in pregnancy has increased significantly in the past 10 years. Women with OUD may often be undertreated or untreated because of limited accessibility to treatment, particularly in rural areas. Because detoxification is not recommended during pregnancy due to the potential for adverse outcomes in the fetus and a high risk of relapse for the woman, more primary care providers need to be well versed in opioid‐assisted therapy. In addition, recent changes in Food and Drug Administration regulations now allow nurse practitioners and physician assistants with specialized training to provide buprenorphine treatment for pregnant women with OUD in primary care settings. The purpose of this article is to provide information and guidance for clinicians working with and treating this population.